1.8 Ga magmatism in southern Finland: Strongly enriched mantle and juvenile crustal sources in a post-collisional setting - Rutanen H; Andersson U; Väisänen M; Johansson A; Fröjdö S; Lahaye Y; Eklund O (Taylor & Francis, 2025)
Whole-rock and isotope geochemistry of six 1.8 Ga post-kinematic intrusions, emplaced along the 1.9 Ga Southern Svecofennian Arc Complex (SSAC) and in the SW part of the Karelian Domain in Finland, was studied. The intrusive age [U-Pb secondary ion mass spectrometer (SIMS)] of one of these, the Petravaara Pluton, was determined as 1811 ± 6 Ma. Basic-intermediate rocks are alkali-rich (KO + NaO 4 wt.%) and typically shoshonitic, strongly enriched in large ion lithophile elements and light rare earth elements, but relatively depleted in high field strength elements and heavy rare earth elements. The enrichment is much higher than can be accounted for by crustal contamination and requires previously melt-depleted mantle sources, subjected to variable metasomatism by carbonate-rich fluids and sediment-derived melts. These sources are inferred to consist of phlogopite amphibole-bearing peridotites from depths below the spinel-garnet transition, as shown by the high Ce/Yb ratios. Sr/Sr(1.8 Ga) ratios in the range 0.7027-0.7031 and 'mildly depleted' ε(1.8 Ga) values (+0.1 to +1.4), with T values < 2.1 Ga, suggest that mantle enrichment was associated with the previous Svecofennian subduction-accretion process, when enriched sub-Svecofennian mantle sections developed, dominantly characterized by Sm/Nd ratios of 0.14-0.17. The associated granitoids are diversified. One group is marginally peraluminous, transitional between I (volcanic-arc) and S (syn-collisional) types, and was derived from mixed igneous and sedimentary, but juvenile Svecofennian source rocks, as supported by near-chondritic Nd(1.8 Ga) and somewhat elevated Sr/Sr(1.8 Ga). The other group is transitional between I and A (within-plate) types in character and had dominantly igneous protoliths. The whole-rock geochemistry and isotopes suggest that the compositional variation between 50 and 70 wt.% SiO2 may be explained by hybridization between strongly enriched mantle-derived magmas and anatectic granitic magmas from the juvenile Svecofennian crust. One intrusion in the east contains a significant portion of Archaean, mostly igneous protolithic material (ε(1.8 Ga) = -2.8 and ε(t) for zircons between +2.8 and -11.9, with an average of -4.9). The ∼1.8 Ga post-kinematic intrusions were emplaced within the SSAC subsequent to the continental collision with the Volgo-Sarmatia craton from the SE, during a shift from contraction to extension, that is, in a post-collisional setting. © 2010 Taylor & Francis.